Vermicomposting of Leaf Litter Bombax Ceiba by using Epigeic Earthworm Eudrilus Eugiene (International Journal of Food and Nutritional Sciences, 2023)
Vermicompost considered as an excellent product since it is homogenous, has desirable aesthetics, has reduced level of contaminates, has plant growth hormones, higher level of soil enzymes, greater microbial population and tends to hold more nutrients over a longer period without adversely impacting the environment. A study has been conducted to assess the role of vermicomposting and carrying out plant nutrients analysis of composts delivered from leaf litter waste. Wastes were collected and subjected to pit- and vermi-composting using an exotic species of earthworm (Eudrilus eugeniae). Aim of this paper to generate awareness in peoples towards simple method (vermicomposting) for clean up their surrounding through convert waste in to best. This approach was used in present study to decompose leaf waste of college campus in to valuable product. Leaf waste was crushed and mixed with cattle dung in a ratio of 50: 50. At the end of decomposition, vermicompost obtained in fine granular form which was harvested through fine sieve to get homogenous compost. The composts were harvested and analyzed for macro-nutrients (N, P, K, Mg, Ca, S) by employing the standard methods.